Tyrosine kinase inhibitors and signal transduction: molecular biology and latest data - Constantine Zografos, George; John Domeyer, Philip (Contemporary Oncology/Współczesna Onkologia, 2005)
Over the last decades, many discoveries have been made concerning the genetic defects involved in tumor formation and growth. This has launched the development of novel anticancer agents, interfering with the proteins encoded by the identified mutated genes. The bcr-abl gene is considered to be a prototypic tyrosine kinase oncogene. Signal transduction inhibitors target deregulated intracellular pathways. Uncontrolled signal transduction has important deregulatory consequences and is responsible for deranged cellular proliferation, apoptosis, cytoadhesion and ultimately oncogenesis. The efficacy of a recently approved drug named STI571 (Gleevec) in treating patients with chronic myeloid leukaemia gives new hopes to the scientific community to combat cancer. STI571 has proved to be very effective in killing Bcr-Abl-positive cells in vitro and in vivo , both in chronic or stable phase disease and in blast crisis phase of chronic myelogenous leukemia as well as in Ph+ acute lymphocytic leukemia (ALL). The discovery of STI571 is considered as the hallmark of a new beginning in drug therapy. It is believed that a growing number of new molecular targets will soon emerge. In this article we present a brief review of the signal transduction pathway and explain the philosophy of the signal transduction inhibitors, focusing on the newly discovered drug STI571 (Gleevec).